Tensions, emotions and learning in university students in times of pandemic - Guerrero Azpeitia, Luis Arturo (2021)
In this research, the objective was to describe the perceptions that university students manifest of their formative process when moving from a face-to-face modality to a virtual one in the time of the SARS-CoV2 pandemic. The object of study was constructed from a sociological perspective that associated objective conditions and the corresponding production of subjectivities. Methodologically, three moments were recovered: 1) determination of social and technological capital; 2) construction of social classes from the determination of the volume and structure of capital; and 3) detection of student perceptions. The results (Cronbach's alpha of 0.913) establish that the lower the volume and structure of the students, the lower the academic performance, the less proclivity to an online work, the greater the need for academic accompaniment and the lower the institutional follow-up. By way of conclusion, an accentuation of the conditions of disadvantage in those vulnerable groups is identified.